Пинч-диагностика и моделирование процесса разделения широкой фракции легких углеводородов - Ульев, Леонид Михайлович; Поливода, Е. В. (НТУ "ХПИ", 2010)
Simulation of light hydrocarbons wide fraction separation process with the help of UniSim Design al-lows us to improve the found data and to receive missing data. Using the UniSim Design thermodynamic models let us to calculate of physical properties and phase equilibrium with good precision. This gives possibility to write stream table and to build the composite curves. Energy saving potential was found with the help of compo-site curves. The retrofit project of heat exchange network was made in this paper. UniSim Design simulation showed the availability of the new project for CGFU heat network. Implementation of this project will give 492100 US dollars of profit, with the payback period equal 5 months
Keywords: переработка углеводородного сырья; энергоносители; конденсация паров; потребление тепловой энергии